Media Pembelajaran Global Warming - Fikri Jufri Tham; Liliana Liliana; Kristo Radion Purba (Jurnal Infra, 2016)
Computer based learning media is one of the media has an important role in learning. Learning media will be attractive when packaged through interactive media , such as interactive media created in paper manufacture " instructional media global warming" . The advantage gained is that it can increase knowledge, generally educate people to be more concerned about the environment , and also can be a means of entertainment. This application is focused to learn about global warming and packaged in the form of interesting and interactive . Ranging from simulations that show the cause of global warming , global warming impacts and solutions of global warming and there is a mini- game that is packaged in the form of adventure game to make it look attractive and there is a global warming materials that can add insight . This application is created using Adobe Flash Professional CS6 .Based on tests performed and result of the questionnaries to prove that the application and the simulation strongly supports the process of understanding the material.therefore user’s interest in learning is increased, coupled with the mini game will make this application even more appealing.